The relationship between CRM and innovation capability : the mediating role of dynamic capabilities - Araujo, Cintia Cristina S. de (2018)
Innovation is a top priority for many organizations as a way to achieve superior competitive advantage. In the chase to be more innovative, organizations are playing more attention to how they can develop innovation capability. The purpose of this paper is to evaluate the mediating effect of dynamic capability (DC) on the relationship between Customer Relationship Management (CRM) and innovation capability. Structural equation modelling is used to test the research hypotheses based on a sample of 234 respondents in Brazil. The questionnaire was addressed to CRM, Marketing and Information Technology Managers. Results suggest that CRM enhances innovation capability through the partial mediation of dynamic capability. This means that for organizations to develop innovation capability from CRM adoption, they should develop dynamics capabilities so they can sense, seize and reconfigure organizational resources and processes. Findings suggest that organizational innovation capability depend on the continuous ability to rearrange resources and assets used by CRM adoption. This study is the first to point out that CRM cannot bring innovation capability in itself. For organizations to develop innovation capability, they need to combine CRM with dynamic capabilities